2014
DOI: 10.1108/sbm-12-2013-0044
|View full text |Cite
|
Sign up to set email alerts
|

Sport sponsorship alliances: relationship management for shared value

Abstract: is an academic in the Management Discipline Group at the UTS Business School. Ashlee has recently completed her PhD in sport management, examining the governance of corporate sport sponsorship. Her research interests are in strategic alliances, business-tobusiness relationships and sport sponsorship. Daryl Adair is Associate Professor in the Management Discipline Group at the UTS Business School. He is on the editorial board of several academic sport journals. His most recent book (with Stephen Frawley) is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 38 publications
(48 reference statements)
0
17
0
Order By: Relevance
“…Furthermore they also argue that value-added benefits of both parties and the continuum of relationships are essential for understanding sponsor-club relations (Cousens et al, 2006). This continuum is found to be depending on inter-personal relationships rather than inter-organisational relationships and fulfilment of mutual and individual expectations on the sponsor agreement (Morgan et al, 2014). Sponsorship relationships are going through a life cycle including three stages: formation, operation and outcome.…”
Section: The Relational Paradigmmentioning
confidence: 99%
“…Furthermore they also argue that value-added benefits of both parties and the continuum of relationships are essential for understanding sponsor-club relations (Cousens et al, 2006). This continuum is found to be depending on inter-personal relationships rather than inter-organisational relationships and fulfilment of mutual and individual expectations on the sponsor agreement (Morgan et al, 2014). Sponsorship relationships are going through a life cycle including three stages: formation, operation and outcome.…”
Section: The Relational Paradigmmentioning
confidence: 99%
“…They found that strong relationships helped with the formal execution of the agreement and decisionmaking on activation and other issues that arose. Staff turnover was detrimental to satisfaction (34). The sponsors highly valued informal interpersonal relationships with the sport organization feeling they enhanced the ability to manage the formalities of the business agreement.…”
Section: Sponsorship and Organizational Culture Kevin Heiseymentioning
confidence: 99%
“…The sponsors highly valued informal interpersonal relationships with the sport organization feeling they enhanced the ability to manage the formalities of the business agreement. The commercial director of the sport organization indicated that he feels the relationships between people drive successful sponsorships (34).…”
Section: Sponsorship and Organizational Culture Kevin Heiseymentioning
confidence: 99%
See 1 more Smart Citation
“…Meenaghan and Shipley (1999, p. 335) IJSMS define sponsorship as a "symbiotic relationship with a transference of inherent values from the activity to the sponsor." Hence, no sponsorship can be successful without the existence of productive relationships (Morgan et al, 2014). In fact, the sponsor and the sponsee are more likely to gain full benefit of their agreement if they work together collaboratively in a long-term alliance (Chadwick, 2002).…”
Section: Theorymentioning
confidence: 99%